Resale Price Maintenance after Leegin: Behavioral, Evolutionary, and Institutional Insights for Advancing the Free Rider Thesis. (September 2017) - Gundlach, Gregory T.; Manning, Kenneth C.; Cannon, Joseph P.
Resale price maintenance (RPM) is a controversial channel pricing strategy that restricts the price at which a product can be resold. Contemporary understanding of RPM is derived mainly from economics, in which various perspectives have been applied to explain its use and effects. Motivated by a recent Supreme Court decision that altered prior restrictions on the use of minimum RPM, the authors propose three new perspectives and related theoretical propositions to enhance understanding of the primary procompetitive explanation of minimum RPM: the free rider thesis. The perspectives and propositions advance knowledge of RPM in ways that are important to academic scholarship, public policy, and managerial practice.